Functional CVIDs phenotype clusters identified by the integration of immune parameters after BNT162b2 boosters - Piano Mortari, Eva; Pulvirenti, Federica; Marcellini, Valentina; Terreri, Sara; Salinas, Ane Fernandez; Ferrari, Simona; Di Napoli, Giulia; Guadagnolo, Daniele; Sculco, Eleonora; Albano, Christian; Guercio, Marika; Di Cecca, Stefano; et al. (Frontiers in Immunology, 2023)
Functional CVIDs phenotype clusters identified by the integration of immune parameters after BTN162b2 boostersAssessing the response to vaccinations is one of the diagnostic criteria for Common Variable Immune Deficiencies (CVIDs). Vaccination against SARS-CoV-2 offered the unique opportunity to analyze the immune response to a novel antigen. We identify four CVIDs phenotype clusters by the integration of immune parameters after BTN162b2 boosters. We performed a longitudinal study on 47 CVIDs patients who received the 3rd and 4th vaccine dose of the BNT162b2 vaccine measuring the generation of immunological memory. We analyzed specific and neutralizing antibodies, spike-specific memory B cells, and functional T cells. We found that, depending on the readout of vaccine efficacy, the frequency of responders changes. Although 63.8% of the patients have specific antibodies in the serum, only 30% have high-affinity specific memory B cells and generate recall responses. Thanks to the integration of our data, we identified four functional groups of CVIDs patients with different B cell phenotypes, T cell functions, and clinical diseases. The presence of antibodies alone is not sufficient to demonstrate the establishment of immune memory and the measurement of the in-vivo response to vaccination distinguishes patients with different immunological defects and clinical diseases.